M13 Clinical characteristics and management of patients presenting to the "Airways Clinic"; a specialised tertiary multi-disciplinary respiratory service. (12th November 2015) - Haines, J; Vyas, A; Slinger, C; Cheyne, N; Fowler, SJ
Abstract : Introduction: Our specialist service manages patients with vocal cord dysfunction (VCD), chronic cough (CC) and dysfunctional breathing (DB), and referrals have grown exponentially since we introduced this novel multi-disciplinary (MDT) model in 2006. The team comprises two severe asthma specialist physicians, two respiratory speech and language therapists (rSLT), a severe asthma nurse specialist, respiratory physiotherapist and clinical psychologist. Aims: To describe the clinical characteristics of those referred and assess utilisation of the multi-disciplinary structure. Methods: Patient demographics and clinical data were retrospectively collated from clinical records of patients referred between January and December 2014. Results: The service received 249 referrals. Excluding patients still in treatment or who failed to attend initial assessment, 141 complete data sets were available for analysis: 71% female; mean (range) age 55 (18–79) years. Assessment requests were for VCD (71%), CC (28%) or both (1%) and over half were from NW severe asthma centres or extra-regional specialist centres. The majority of referrals were from hospital consultants (72%), with the remainder from GPs (17%) and AHPs (11%). For VCD there was 73% agreement between the clinical suspicion on referral and nasendoscopic assessment. Approximately half had evidence of co-existent reflux (52%) and a third (29%) had nasal disease. The majority were seen by more than one member of the MDT team; all by a specialist physician and a rSLT, 43% by respiratory physiotherapy, and 7% clinical psychology. In the VCD cohort 64% had a previous asthma diagnosis and this was confirmed in the majority (93%) – 49(82%) were ≥Step 3 on BTS/SIGN guidelines; 43% were additionally referred for DB assessment; 78 flow volume loops were available and 31 (40%) were suggestive of extra thoracic inspiratory airway obstruction. Sixty-seven patients (48%) received rSLT management [median (range) 4(1–8) sessions] with a further 16(11%) scheduled to receive it post medical intervention. Of those who completed treatment, 63% had clinically improved presentation on discharge nasendoscopy. Conclusions: A large proportion of patients referred to a specialist service for patients with complex breathlessness require multi-disciplinary intervention. There is a significant incidence of VCD and DB in patients with severe complex asthma. Of those receiving rSLT interventions, outcome was extremely effective at reducing symptoms.